2020
DOI: 10.3390/ijerph17051568
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity against Staphylococcus Aureus of Titanium Surfaces Coated with Graphene Nanoplatelets to Prevent Peri-Implant Diseases. An In-Vitro Pilot Study

Abstract: Dental implants are one of the most commonly used ways to replace missing teeth. Nevertheless, the close contact with hard and soft oral tissues expose these devices to infectious peri-implant diseases. To prevent such infection, several surface treatments have been developed in the last few years to improve the antimicrobial properties of titanium dental implants. In this in-vitro pilot study, the antimicrobial activity of titanium surfaces coated with different types of graphene nanoplatelets are investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…In particular, recent scientific breakthroughs have demonstrated that GNPs, in addition to their significant physiochemical properties, show great antimicrobial effects [ 9 ], without exerting relevant cytotoxic damages on human cell lines [ 10 ]. However, based on the available literature data, owing to the high uncertainty and the numerous conflicting outcomes about the hazardous properties of graphene nanomaterials [ 11 , 12 , 13 ] and their possible effects on humans’ health [ 14 ], specific occupational exposure limits are not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, recent scientific breakthroughs have demonstrated that GNPs, in addition to their significant physiochemical properties, show great antimicrobial effects [ 9 ], without exerting relevant cytotoxic damages on human cell lines [ 10 ]. However, based on the available literature data, owing to the high uncertainty and the numerous conflicting outcomes about the hazardous properties of graphene nanomaterials [ 11 , 12 , 13 ] and their possible effects on humans’ health [ 14 ], specific occupational exposure limits are not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…They have also noted that the number of attached bacteria was variable among the films, with a higher amount being found on smoother surfaces, i.e., pyrolytic graphite surfaces used as control. Pranno et al (2020) used LPE graphene to improve antimicrobial properties of titanium dental implants, commonly exposed to infections. The graphene flakes were then applied as a coating on the titanium.…”
Section: Dm Coatings and Cellular Interactionmentioning
confidence: 99%
“…The graphene flakes were then applied as a coating on the titanium. The lowest % of S. aureus biofilm formation was observed in samples with the smaller flake size (obtained with the longest sonication times) ( Pranno et al, 2020 ). Besides bacteria, a physical disruption mechanism has also been recently observed in the case of virus, again via the contact with sharp edges in graphene ( Innocenzi and Stagi, 2020 ).…”
Section: Dm Coatings and Cellular Interactionmentioning
confidence: 99%
“…These layers are approximately 1 nm thick and 400–500 mm long, having a very high aspect ratio [ 67 ]. Several groups have investigated the GO coating of Ti implants in order to improve the osseointegration since it is biocompatible, has antibacterial properties [ 68 ] and can enhance the mechanical properties [ 69 ]. In addition, GO coatings prevent corrosion [ 70 ].…”
Section: Graphenementioning
confidence: 99%